Smart Cities and Smart Tourism: Responding to the Demands of Modern Urbanization - Rakhi Aditya Begampure (AG Volumes, 2026)
In the fast-moving developmental world, the role of information and communication technology become very essential in almost all industries. Smart technologies reach into almost all aspects of life nowadays, although they are often unnoticed by users and taken for granted. Recently, tourism destinations have also started to implement smart technologies with the intention to enhance the experience of incoming tourists in response to the new EU goals to limit the ongoing climate change (Endesa, 2008). The technological advancement and immense use of ICT in tourism directs smart tourism in that direction only, even it has some other dimensions. Smart tourism also directs towards the innovative use of technology in resource optimisation, sustainability, good governance, and quality of life in the tourism industry. This paper defines smart cities and smart tourism and their importance and relevance todays context. Smart tourism is a rapidly growing concept in developed countries and in developed smart cities. The study focuses on the smart tourism practices in the smart city and, importantly, the prospects and challenges that come in the way of smart tourism are also discussed. This paper extends the previous research on smart tourism and draws attention to further study on smart tourism development and management.